PENGEMBANGAN MEDIA KAHOOT UNTUK PEMBELAJARAN PKN DI KELAS TINGGI SEKOLAH DASAR: ABSTRACT,PENDAHULUAN,METODE,HASIL DAN PEMBAHASAN, KESIMPULAN,DAFTAR RUJUKAN - Aditra Zulfi; Miaz, Yalvema; Erita, Yeni; Alfarisi Nirya, M Haikal; Oktaviandi, Jefri (Journal of Practice Learning and Educational Development, 2026)
Education is fundamentally a gateway for students to acquire new insights, including comprehending the reality of diversity in Indonesia. Awareness of this multicultural society must be cultivated from an early age to foster mutual respect and prevent social friction. Under the current curriculum, Civics Education (PPKn) does not merely teach citizenship theory but also emphasizes character education. Based on Law No. 20 of 2003, values such as integrity, mutual cooperation, and nationalism must be instilled in students. The urgency of character education becomes increasingly apparent when facing a social reality fraught with conflict, such as the prevalence of bullying, sexual violence, and the erosion of empathy for others. Civics Education at the elementary school level plays a vital role as the foundation for developing students' knowledge and social skills. The utilization of digital media such as Kahoot becomes the key to creating interactive and technology-based learning. This medium offers a game-based quiz approach that is effective in fostering students' interest and focus on the subject matter. Furthermore, Kahoot possesses comprehensive evaluation features this medium is highly useful for supporting various academic activities, such as practice exercises, enrichment programs, and measuring learning outcomes through pretests and posttests.